Isometric midthigh pull performance is associated with athletic performance and sprinting kinetics in division I men and women's basketball players - Townsend, J. R.; Bender, D.; Vantrease, W. C.; Hudy, J.; Huet, K.; Williamson, C.; Bechke, E.; Serafini, P. R.; Mangine, G. T. (The Journal of Strength and Conditioning Research, 2019)
The relationships between isometric mid-thigh pull (IMTP) force, athletic performance measures, and sprint kinetics in Division I men's and women's basketball players were investigated. Twenty-three (male = 8, female = 15) Division 1 basketball players completed a maximal 20-m sprint trial while tethered to a device that provided kinetic feedback (peak and average sprinting power, velocity and force). Additionally, 1 repetition maximum (1RM) front squat, 1RM hang clean, vertical jump height, and agility (proagility and lane agility) tests were performed. Rate of force development (RFD) at 50, 100, 150, 200 and 250 milliseconds of IMTP and peak force (PF) were also collected. Pearson's product-moment correlation analysis was used to examine the relationships between these measures. Significant (p ? 0.05) relationships were observed between IMTP PF and sprint time over all distances (5-20 m; r = ?0.62 to 0.69), average sprint velocity (r = 0.50-0.70), peak sprint velocity (r = 0.50-0.54), average sprint force (r = 0.48-0.69), and average sprint power (r = 0.62-0.73). Sprinting kinetic measures (average force and power) over the first 5 m were also significantly (p ? 0.05) related to IMTP RFD (50-250 ms; r = 0.42-0.62). Results indicate that IMTP variables are significantly associated with 20-m sprint kinetics. Specifically, IMTP RFD appears to be related to the initial acceleration kinetics of a sprint. Strength and conditioning professionals can possibly implement the IMTP for improved assessment and monitoring of athletic performance and training.